Identify of The Dropping in Hydrophore Tank Pump Pressure At Mt. Inter Armada 01 - Mustholiq, Mustholiq; Kensiwi, Fitri; Pangestu, Wisnu Ageng (RSF Conference Series: Engineering and Technology, 2023)
A hydrophore tank or water pressure tank is a tank that stores water temporarily and then separates water and air through a membrane so that the air in it is compressed. The water in the tank is flowed into a distribution building. The pump works automatically, regulated by a pressure detector, which closes/opens the electric motor’s switch driving pump. The pump stops working when the pressure in the tank reaches a specified minimum. In this system, the compressed air will press water into the distribution system. After repeatedly expanding and compressing over time, it will decrease because it dissolves in water or is carried out of the tank. Pressure tank systems are usually designed so that the air volume is no more than 30% against the volume of a 70% tank filled with water. Factors causing pressure drops in the hydrophore tank pump at MT. Inter Armada 01 is a PMS that is not carried out properly; packing is impermeable, and the fresh water pump does not work normally. The impact of the lack of pressure on the hydrophore tank is the lack of fresh water supply to the accommodation and disruption of the crew’s comfort. How to prevent pressure drops on the hydrophore tank is to replace damaged components with new ones according to the manual book periodically check the components and systems of the hydrophore tank so that the hydrophore tank system can run properly and normally again. The method used in this thesis is a qualitative descriptive method with SHEL analysis techniques as a method to determine the cause and efforts to overcome it. The formulation of the problem from this study is the factors causing the lack of pressure on the hydrophore tank, the impact caused by the lack of pressure on the hydrophore tank, and the efforts that must be made to overcome the pressure drop in the hydrophore tank.